The Importance of Interaction for Academic Success in Online Courses with Hearing, Deaf, and Hard-of-Hearing Students - Long, Gary L.; Marchetti, Carol; Fasse, Richard (International Review of Research in Open and Distributed Learning, 2011)
This paper reports the findings of three studies within a program of research designed to better understand the factors contributing to the academic achievement of students in online courses and the contributions of interaction to online learning. The first study compared the academic achievement of students in the online and face-to-face (F2F) sections of multiple courses. In the second study, an online survey was used to obtain student perceptions of course satisfaction, learning, and communication. These factors were then related, using binary logistic regression analysis, to the amount of interaction that occurred in the students’ respective online courses; information from the myCourses course management system was used to quantify the amount of interaction that occurred in online courses. In the final study, both datasets were used to examine the academic achievement of students in online courses based upon the amount of interaction that had actually occurred. Whenever possible, a subgroup of deaf and hard-of-hearing students was included in the study to increase our understanding of the role that communication plays in the teaching-learning process. Our findings indicate that students enrolled in online courses, especially those designed with high levels of online interaction, receive higher grades and report greater learning than students in comparable F2F courses. In addition, online courses appear to provide deaf and hard-of-hearing students with special benefits in terms of academic achievement through online discussion. Overall, the studies illuminate how the quantity of interaction in online discussions relates to important success factors. Students in online courses with more interaction outperformed students in online courses with less interaction.